Unemployment and Rural-Urban Migration: The Impact of Energy Taxes on Rural-Urban Migration and Labor Market Outcomes (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper constructs a general model of equilibrium that integrates particular features of developed countries a broad informal sector and urban-rural migration. A calibrated variant of the model is used to research the impact of shifts in energy taxes and a decrease in energy incentives in the agriculture sector on labor market outcomes. The findings show that, by rural – urban migration, the incidence of energy taxes is transferred in part to rural market. The findings thus stress the value of modeling the characteristics unique to developed countries and the general effects of economic equilibrium while determining the influence of environmental taxation in developing countries.